“Augmentative and Alternative Communication (AAC) Will Give You a Voice”: Key Practices in AAC Assessment and Intervention as Described by Persons with Amyotrophic Lateral Sclerosis - McNaughton, David; Giambalvo, Felicia; Kohler, Kim; Nazareth, Godfrey; Caron, Jessica; Fager, Susan (Seminars in Speech and Language, 2018)
The purpose of this study was to describe the perceptions of persons with amyotrophic lateral sclerosis (pALS) who use augmentative and alternative communication (AAC) with the AAC assessment and intervention process. Twenty-one pALS with complex communication needs participated in a multipart survey (and follow-up e-mails) to provide information on their experiences with AAC assessment and intervention. A majority of the participants agreed with the importance of three key AAC intervention principles: appropriate staging of the timing of assessment and intervention activities, inclusion of communication partners, and the use of multiple modalities and strategies as communication supports. Most participants reported that their assessment and intervention experiences included at least some aspect of these three key practices. The results of this study suggest that the identified best practices in AAC should be reviewed and implemented on an individualized basis for pALS with complex communication needs.
Keywords: augmentative and alternative communication; amyotrophic lateral sclerosis; communication; assistive technology